Smart rogaining for computer science orientation - Chessa, Manuela; Delzanno, Giorgio; Ferrando, Angelo; Gelati, Luca; Guerrini, Giovanna; Mascardi, Viviana; Noceti, Nicoletta; Odone, Francesca; Vitali, Francesca (Frontiers in Education, 2022)
We present a teamwork format for orientation to computer science that exploits gamification principles by means of rogaining activities enhanced with specifically devised smart applications based on mobile and web apps. The format is based on a rogaine that offer engaging introductory activities to prospective computer science students dislocated along the different stages of the competition. The format is aimed at stimulating the interest of participants in different areas of computer science and at improving digital and soft skills of participants and, as a side effect, of staff members (teachers and university students). In the paper we introduce the proposed format of teamwork activity and discuss our experience in the 2019 and 2020 editions at the University of Genoa with 135 and 62 participants, respectively. \